Hydroxyapatite–Bovine Serum Albumin–Paclitaxel Nanoparticles for Locoregional Treatment of Osteosarcoma. Issue 2 (9th November 2020) - Liu, Yongjia; Qiao, Zhiguang; Gao, Jian; Wu, Fengren; Sun, Binbin; Lian, Meifei; Qian, Jiwen; Su, Yue; Zhu, Xinyuan; Zhu, Bangshang
Abstract: Osteosarcoma is the most primary type of bone tumor occurring in the pediatric and adolescent age groups. In order to obtain the most appropriate prognosis, both tumor recurrence inhibition and bone repair promotion are required. In this study, a ternary nanoscale biomaterial/antitumor drug complex including hydroxyapatite (HA), bovine serum albumin (BSA) and paclitaxel (PTX) is prepared for post‐surgical cancer treatment of osteosarcoma in situ. The HA–BSA–PTX nanoparticles, about 55 nm in diameter with drug loading efficiency (32.17 wt%), have sustained release properties of PTX and calcium ions (Ca 2+ ) and low cytotoxicity to human fetal osteoblastic (hFOB 1.19) cells in vitro. However, for osteosarcoma (143B) cells, the proliferation, migration, and invasion ability are significantly inhibited. The in situ osteosarcoma model studies demonstrate that HA–BSA–PTX nanoparticles have significant anticancer effects and can effectively inhibit tumor metastasis. Meanwhile, the detection of alkaline phosphatase activity, calcium deposition, and reverse transcription‐polymerase chain reaction proves that the HA–BSA–PTX nanoparticles can promote the osteogenic differentiation. Therefore, the HA–BSA–PTX nanodrug delivery system combined with sustained drug release, antitumor, and osteogenesis effects is a promising agent for osteosarcoma adjuvant therapy. Abstract : In this article, a novel ternary nanoscale biomaterial/antitumor drug delivery system (HA–BSA–PTX nanoparticles) is proposed and used for post‐surgical cancer treatment of osteosarcoma in situ. The HA–BSA–PTX nanodrug complex possessing high drug load efficacy, sustained drug release, antitumor and osteogenesis effects, is a potential nanomedicine for osteosarcoma adjuvant therapy.